Determination of Electric and Magnetic Field Calculation Uncertainty in the Vicinity of Overhead Transmission Lines - Alihodzic,Ajdin (2022)
Abstract This paper presents a new approach for uncertainty determination of the electric field intensity and magnetic flux density calculation in the vicinity of overhead transmission lines. The proposed method is based on the law of propagation of uncertainty as defined in the Guide to the expression of Uncertainty in Measurement. A mathematical model is developed for determining the electric field intensity and magnetic flux density calculation uncertainty based on the Charge simulation method and method based on Biot – Savart law, respectively. The verification of the proposed method was performed by estimating the uncertainty of the electric field and magnetic flux density calculations for four single circuit and two double circuit high-voltage overhead transmission lines. The analysis of the obtained results demonstrates that the proposed method can be successfully used to determine the uncertainty of electric field intensity and magnetic flux density calculations in the vicinity of overhead transmission lines.